Characterization of a temperature-sensitive, hexon transport mutant of type 5 adenovirus. - Kauffman, R S (1976)
Infection of KB cells at 39.5 degrees C with H5ts147, a temperature-sensitive (ts) mutant of type 5 adenovirus, resulted in the cytoplasmic accumulation of hexon antigen; all other virion proteins measured, however, were normally transported into the nucleus. Immunofluorescence techniques were used to study the intracellular location of viral proteins. Genetic studies revealed that H5ts147 was the single member of a nonoverlapping complementation group and occupied a unique locus on the adenovirus genetic map, distinct from mutants that failed to produce immunologically reactive hexons at 39.5 degrees C ("hexon-minus" mutants). Sedimentation studies of extracts of H5ts147-infected cells cultured and labeled at 39.5 degrees C revealed the production of 12S hexon capsomers (the native, trimeric structures), which were immunoprecipitable to the same extent as hexons synthesized in wild type (WT)-infected cells. In contrast, only 3.4S polypeptide chains were found in extracts of cells infected with the class of mutants unable to produce immunologically reactive hexon protein at 39.5 degrees C. Hexons synthesized in H5ts147-infected cells at 39.5 degrees C were capable of being assembled into virions, to the same extent as hexons synthesized in WT-infected cells, when the temperature was shifted down to the permissive temperature, 32 degrees C. Infectious virus production was initiated within 2 to 6 h after shift-down to 32 degrees C; de novo protein synthesis was required to allow this increase in viral titer. If ts147-infected cells were shifted up to 39.5 degrees C late in the viral multiplication cycle, viral production was arrested within 1 to 2 h. The kinetics of shutoff was similar to that of a WT-infected culture treated with cycloheximide at the time of shift-up. The P-VI nonvirion polypeptide, the precursor to virion protein VI, was unstable at 39.5 degrees C, whereas the hexon polypeptide was not degraded during the chase. It appears that there is a structural requirement for the transport of hexons into the nucleus more stringent than the acquisition of immunological reactivity and folding into the 12S form.